Endophytic Microbial Inoculation Modulates Plant Defense Responses and Growth Performance - Sindhuja Suram; Poly Saha; Abhijit Debnath; A. K. Mohanty; Chakpram Birendrajit; Athokpam Haribhushan; Lahar Jyoti Bordoloi; Moaakum Pongen (Public Health, 2026)
Endophytic microorganisms inhabit internal plant tissues without causing visible disease and can substan- tially modify plant growth, immunity, nutrient acquisition and tolerance to environmental stress. Their effects arise from coordinated interactions among microbial colonization traits, plant immune surveillance, phytohormonal signalling, redox regulation, nutrient exchange and resident microbial communities. Endo- phytes are not immunologically invisible; rather, successful strains regulate the amplitude, duration and spatial distribution of pattern-triggered immunity. Controlled immune accommodation permits internal colonization, whereas reactive oxygen species, mitogen-activated protein kinase cascades and specialized metabolites constrain excessive microbial proliferation. Many endophytes simultaneously prime systemic tissues through jasmonic acid, ethylene, salicylic acid and N-hydroxypipecolic acid-associated pathways, enabling faster defence activation after pathogen challenge without the metabolic cost of constitutive resistance. Growth promotion results from microbial auxin production, 1-aminocyclopropane-1-carboxylate deaminase activity, biological nitrogen fixation, phosphorus transfer, siderophore production, improved root architecture and maintenance of photosynthesis under stress. Representative systems include Bacillus velezensis FZB42, Enterobacter sp. SA187, Paraburkholderia phytofirmans PsJN, Colletotrichum tofieldiae, Serendipita indica and endophytic Beauveria, Metarhizium and Epichloë species. Synthetic communities and bacterial–fungal combinations can broaden disease suppression and environmental stability, although strain identity and functional compatibility are often more important than taxonomic richness. Multi-omics, spatial imaging, stable-isotope tracing and synthetic biology are improving mechanistic resolution, while encapsulation and hydrogel technologies are enhancing inoculant delivery. However, field performance remains constrained by host genotype, resident microbiota, formulation, environmental variability and biosafety concerns. This review integrates current understanding of endophyte diversity, colonization, immune modulation, growth promotion, stress adaptation and field translation, emphasizing the need for mechanism-guided, ecology-aware and genomically validated inoculant development.